2018
DOI: 10.1111/joor.12753
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of maxillary sinus floor augmentation without grafts in atrophic maxilla: A systematic review and meta‐analysis based on randomised controlled trials

Abstract: Summary Background Maxillary sinus floor augmentation without grafts has been more widely used, but the efficacy is still controversial. Purpose The aim of this review was to systematically evaluate the effectiveness of sinus floor augmentation without grafts in atrophic maxilla. Methods The electronic databases included PubMed, EMBASE and the Cochrane Central Register of Controlled Trials. The meta‐analysis was conducted by Review Manager 5.1. The quality of evidence was assessed using the Grades of Recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…This result is in agreement with several reviews in the literature (Moraschini, Uzeda, Sartoretto, & Calasans‐Maia, 2017; Nasr, Slot, Bahaa, Dorfer, & Fawzy El‐Sayed, 2016; Yang, Xia, Wang, Cheng, & Shi, 2019). A recent review compared seven clinical studies using TSFE with and without graft material (Chen & Shi, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with several reviews in the literature (Moraschini, Uzeda, Sartoretto, & Calasans‐Maia, 2017; Nasr, Slot, Bahaa, Dorfer, & Fawzy El‐Sayed, 2016; Yang, Xia, Wang, Cheng, & Shi, 2019). A recent review compared seven clinical studies using TSFE with and without graft material (Chen & Shi, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…However, in a more recent report, the crestal approach was applied with only 2 mm of alveolar bone available [ 13 ]. Sinus augmentation has been performed without graft materials, and a previous study reported no significant difference in short-term implant survival in maxillary sinus augmentation with versus without grafts [ 14 ]. The application of short implants may minimize complications.…”
Section: Discussionmentioning
confidence: 99%
“…Similar long-term outcomes of Astra bone-level implants have been reported with retrospective design (Caban et al, 2017). Recent systematic reviews reported that the short-term and mid-term implant survival rates ranged from 93.5% to 100.0% (Duan et al, 2017;Yang et al, 2019). However, none of the previous studies have reported long-term outcomes of patients with severely atrophic maxilla (residual bone height [RBH] ≤4 mm).…”
Section: Introductionmentioning
confidence: 60%